2022
DOI: 10.1186/s12979-022-00309-5
|View full text |Cite
|
Sign up to set email alerts
|

Aging, inflammaging and immunosenescence as risk factors of severe COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a respiratory infectious disease caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 is characterized by having a heterogeneous disease course, ranging from asymptomatic and mild symptoms to more severe and critical cases. In most cases the severity of COVID-19 is related to host factors, especially deregulation of the immune response in patients. Even if COVID-19 indiscriminately affects individuals of different age group, ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 183 publications
(206 reference statements)
5
31
0
3
Order By: Relevance
“…These data suggest that the effect of a second vaccination on the antibody response depends on the age of the recipient, while a third vaccination induces an antibody response regardless of age, through at least 7 months post-vaccination. Given the high risk of COVID-19 in elderly [ 24 ], administration of a third dose vaccine would therefore be a valuable option especially in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the effect of a second vaccination on the antibody response depends on the age of the recipient, while a third vaccination induces an antibody response regardless of age, through at least 7 months post-vaccination. Given the high risk of COVID-19 in elderly [ 24 ], administration of a third dose vaccine would therefore be a valuable option especially in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…However, aging of the immune system is not solely associated with "lowered" immune effector function. Aging in the immune system is often characterized by hyperreactive immune responses 45 and autoimmune dysfunctions, where the immune system is no longer able to properly discriminate self from non-self, resulting in increased auto-reactivity, ultimately leading to organ failure. Aging in the immune system is further characterized by a generalized, systemic, and chronic low-grade inflammatory state that has been named "inflammaging" 7 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pence [62] concluded that pathological monocyte response in COVID-19 showed a similar pattern to those in aging, suggesting that monocytes may contribute to the disproportionate severity of COVID-19 in older adults. Tizazu et al [63] seconded this finding of proinflammatory monocytes both in aging and in severe COVID-19 cases. The lack of enrichment of STSPR-AD tissues for the heart and kidney signatures in the study by Delorey et al [61] emphasizes the role of monocytes in the age-related pathology of COVID-19.…”
Section: Age Dependency Of a Systemic Sars-cov-2 Responsementioning
confidence: 88%